"Bridging two worlds?": Towards cultural safety within Schools of Nursing in Australian Universities. (March 2022) - Petric, Samantha; Hart, Bethne; Mohamed, Janine
Abstract: Background: Cultural safety has a stronghold within nursing practice and nursing education in Australia and is seen as a philosophy and practice that challenges and refutes previous concepts and frameworks of cultural awareness and cultural competence (Petric, 2019). Cultural safety practices are required for all members of the nursing profession, with a gaze now focused upon Australian Schools of Nursing to demonstrate their commitment and readiness towards cultural safety. Aim: This research study measures the commitment and readiness towards cultural safety within Schools of Nursing in Australian universities. Methods: This research study utilises a quantitative descriptive survey design, inviting the Deans of Schools of Nursing in Australia to respond to a modified Occupational Commitment and Health Professional Program Readiness Assessment Compass (DOH, 2014), that measures the current levels of commitment and readiness towards cultural safety. Findings: This research study provides evidence of cultural safety strategies within Australian Schools of Nursing with leadership and commitment being the highest scoring factor ( M = 34.81; SD 6.34). However, structures towards and support for the implementation of cultural safety strategies and practices were demonstrated as weaknesses ( M = 21.18; SD 4.71). Discussion: There is a valuable opportunity for leadership and knowledge sharing between Schools of Nursing in Australia. The research outcomes highlight the importance for Schools of Nursing to review, reflect upon, and fully implement the Nursing and Midwifery Curriculum Framework (CATSINaM, 2017) and to audit and report levels of cultural safety. Conclusions: There are cultural safety champions and their leadership is important to the continuing development of curricula, organisations and the profession. These individuals' actions must also be reflected within and supported by organisational cultures, as they fundamentally encourage or obstruct the development of cultural safety in nursing students and academics; material, cultural and human resources are fundamental to the transformations towards cultural safety and to the decolonising practices of the nursing profession (Petric, 2019).